Effect of Ni(II) on inflammatory gene expression in THP1 monocytic cells1. Issue 3 (23rd October 2012) - Li, Lei; Drury, Jeanie L.; Zhang, Hai; Sun, Jianxun; DiJulio, Dennis; Chung, Whasun O.; Wataha, John C.
Abstract: Nickel‐containing alloys are in common use for dental restorations, but tend to corrode and release Ni(II) in service. Ni(II) increases secretion of several inflammatory cytokines from activated monocytic cells, suggesting that nickel alloys may exaggerate inflammatory responses in adjacent periodontal tissues. In this work, the effects of Ni(II) on expression of inflammatory cytokine and receptor genes as well as nuclear factor‐kappa B (NFκB)‐related genes were assessed using quantitative real‐time polymerase chain reaction (PCR) and PCR‐based arrays in the human THP1 monocytic cell line pre‐exposed to Ni(II) for 72 h, then activated by lipopolysaccharide. The expression of 10 inflammatory genes was down‐regulated ≥50% by Ni(II) versus non‐Ni(II) controls, whereas some genes like IL8 were up‐regulated significantly by Ni(II). Expression of seven NFκB‐related genes was up‐regulated by Ni(II) by ≥50%, and HMOX1 expression, a redox protein regulated by NRF2, was increased by >500%. The current results suggest that Ni(II) has diverse effects on inflammatory gene expression, which may partly account for previous reports of Ni(II)‐induced changes in inflammatory cytokine secretion from monocytes and alterations in NFκB regulation. Further work is needed to verify these effects in primary cells and to ascertain how Ni(II) alters gene expression. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 902–908, 2013.